FIM Governance and Integrity Centre - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
FIM Governance and Integrity Centre was launched on 15th July 2016 in conjunction with a discussion forum on the topic “Corporate Governance in Malaysia: 18 years after – Where are we heading?” The opening speech was delivered by Prof. Dato’ Daing Nasir Ibrahim, Vice Chancellor, Universiti Malaysia Pahang.